Liszt and the French literary avant-garde o f the 1830s - Gamrat, Małgorzata (Interdisciplinary Studies in Musicology, 2018)
In France the 1820s and 1830s brought about enormous changes in the perception of literature and art as a whole. Young poets, encouraged by the success and novelty of Méditations poétiques by Alphonse de Lamartine, started seeking new possibilities of expression and ways of breaking with the several-centuries-old tradition. They met with a strong protest from conservative milieu, especially those linked to Académie française, and this made them fight for a new paradigm in literature. They eagerly experimented with language as sound (Lamartine, Sainte-Beuve) and graphic (Nodier) matter. They published their texts in the press (Le Globe) and presented them during meetings in artistic salons, which functioned as a kind of laboratory. Thanks to the support of Charles Nodier they could publish their poems in the best publishing houses, which largely contributed to their success. The final victory of the romantics was the premiere of Hernani by Victor Hugo in February 1830. Franz Liszt, who came to Paris in 1823, was an active participant in the artistic and intellectual life there. Moreover, he was also a friend of many prominent artists of the epoch, which can be seen in his letters, writings, and piano music from the early 1830s. A particular example of the relationship between the composer’s music and literary avant-garde is the piece Harmonies poétiques et religieuses of 1835. We find there the domination of the sound element, formal freedom, the intertwining of poetical techniques, experiments with structure, and a strong stress on the word aspect of the oeuvre, for example through very precise notation of tempo markings.